The Cambridge encyclopedia of stage directors - Delgado, Maria M.; Williams, Simon 1943- (Cambridge University Press, 2025)
"With a broader range of entries than any other reference book on stage directors, this Encyclopaedia showcases the extraordinary diversity of theatre as a national and international artistic medium. It covers both individual directors and a range of directorial modes and styles across different global traditions in contemporary theatre"-- Provided by publisher
Includes bibliographical references and index
2505
Keywords: Stage directions / Encyclopedias; Theatrical producers and directors / Encyclopedias; Encyclopedias / http://id.loc.gov/authorities/genreForms/gf2014026092